Multilocus Data Analysis Reveal the Diversity of Cryptic Species in the Tillandsia ionantha (Bromeliaceae: Tillansiodeae) Complex - Juan J. Ancona; Juan P. Pinzón-Esquivel; Eduardo Ruiz-Sánchez; Clarisse Palma-Silva; Juan J. Ortiz-Díaz; Juan Tun-Garrido; Germán Carnevali; Néstor E. Raigoza (Plants, 2022)
Independent evolutionary lineages or species that lack phenotypic variation as an operative criterion for their delimitation are known as cryptic species. However, these have been delimited using other data sources and analysis. The aims of this study are: (1) to evaluate the divergence of the populations of the T. ionantha complex; and (2) to delimit the species using multilocus data, phylogenetic analysis and the coalescent model. Phylogenetic analyses, genetic diversity and population structure, and isolation by distance analysis were performed. A multispecies coalescent analysis to delimit the species was conducted. Phylogenetic analysis showed that T. ionantha is polyphyletic composed of eight evolutionary lineages. Haplotype distribution and genetic differentiation analysis detected strong population structure and high values of genetic differentiation among populations. The positive correlation between genetic differences with geographic distance indicate that the populations are evolving under the model of isolation by distance. The coalescent multispecies analysis performed with starBEAST supports the recognition of eight lineages as different species. Only three out of the eight species have morphological characters good enough to recognize them as different species, while five of them are cryptic species. Tillandsia scaposa and T. vanhyningii are corroborated as independent lineages, and T. ionantha var. stricta changed status to the species level.